Answer:
You didn’t post the figures so I’ll guess C lol
Step-by-step explanation:
Answer:
The factors are 3 and -9
Step-by-step explanation:
The given trinomial is
.
We need to find two factors. We know that,
3(9) = 27
So,
can be written as :
as two factors add up to get -6 and multiply to get -27.
Hence, the factors are 3 and -9.
-4 = y + 3
y = -4x - 3
Solve for Y in the first equation:
-4 = y +3
Subtract 3 from both sides:
y = -7
Now using the addition method:
rewrite the second equation as 4x+y = -3
Multiply y = -7 by - 1 to get -y = 7
Now add the two together:
4x +y = -3
-y =7
4x = 4
Divide each side by 4:
x = 4/4 = 1
Then replace x in one of the equations to solve for y which is -7
X = 1, Y = -7
Answer:
d.24
Step-by-step explanation:
12*2=24 and a negative times a negative always equals a positive.